Rural Employment Evolutions - Elena Faieta; Zhexin Feng; Michel Serafinelli (Institute of Labor Economics (IZA), 2025)
A quarter of the population in high-income countries lives in rural areas. However, existing empirical evidence on these areas in OECD countries is scarce. Over the past several decades, many rural areas have been declining. Nevertheless, it is unclear whether these struggling rural areas are representative of the broad experience of the universe of rural areas. This paper provides a comprehensive analysis of employment evolutions for rural areas in Western Europe during the period 1970–2010. We first analyse 846 rural areas in France, Germany, Italy and the UK, and document large differences in overall employment growth across rural areas in all four countries. A sizable fraction of rural areas lost employment. However, employment in a significant number of rural areas grew during this period. The 90–10 percentile difference in decadal total employment growth of rural areas is 17.4 log points, representing an economically large difference. We then show, using data for Italy and the UK, that changes in the industry structure are fast in rural areas. The estimates also indicate that industry turnover is positively associated with employment growth. Moreover, the evidence shows that areas with stronger total employment growth exhibit stronger employment growth in the manufacturing of food and beverages. All conclusions are similar for rural remote areas. Taken together, our results lend support to the hypothesis that rural economies are not static entities; change is common in these areas, and employment evolutions often result from industry-level dynamics.
Keywords: R12; R32; J21; R11; 330; rural employment; spatial heterogeneity; industry turnover